Integrating Dentists into HPV Vaccine Promotion: A Cross-Sectional Study in a Dental Academic Institution to Address Gaps in Oral and General Health - David Lee; Anita Joy-Thomas; Gisela Bona; Gregory Olson; Alice Pazmino; Lubna Fawad; Ana Neumann (Applied Sciences)
(1) Background: Human Papillomavirus (HPV)-associated oropharyngeal cancer is the fastest-growing head and neck malignancy, yet vaccination coverage remains suboptimal. (2) Methods: In this cross-sectional survey conducted from April 2022 to April 2023, 400 parents of patients aged 8–18 years (mean ± SD = 12.8 ± 2.6; 59.3% female) reported their child’s HPV vaccination status and willingness to initiate or complete the vaccine series at a dental clinic. For those who were not fully vaccinated, reasons for refusal were documented. (3) Results: Over half (54.5%, n = 218) of the children were not fully vaccinated. Notably, 21% (46/218) of parents indicated an immediate willingness to vaccinate their child if the dentist offered it—a significant potential for improvement compared to general healthcare settings. Reported barriers included preference for a physician’s office (43.6%), indecision (20.3%), unspecified concerns (14.5%), safety worries (8.1%), and religious objections (5.2%). Male and younger patients (9–11 years) showed significantly lower vaccination coverage (p < 0.05). (4) Conclusions: Dentists can substantially impact public health by integrating immunization counseling, interprofessional collaboration, and vaccine administration, thereby addressing critical gaps in HPV-related cancer prevention. These findings highlight the opportunity for dental offices to enhance vaccination rates and prompt further research, education, and policy initiatives to advance the oral and general health of our patients.